(untitled) (American Journal of Islam and Society, 2020)
In this paper, I make the case for epistemic relativism: the radical view that all human knowledge/truth is relative. I extend the application of epistemic relativism to include necessary laws such as the laws of logic. I argue that the truth of such laws are relative to human thought, which are ultimately instances derived from our experiences. These experiences act as limitations to which we are conceptually bound. As a result of this, we cannot apprehend God’s omnipotence. This includes God’s maximal power in being able to perform logically impossible actions. Our epistemic inability to conceive of such logically impossible actions is therefore testimony that God transcends the laws of logic.